PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM BASED LEARNING PADA MATERI BILANGAN DI KELAS VII SMP NEGERI 22 KOTA JAMBI - Sri Yulia; Buyung Buyung; Relawati Relawati (PHI: Jurnal Pendidikan Matematika, 2018)
Abstract: Products developed in the form of Student Worksheet (LKS) mathematics on the number material for SMP class VII with problem based learning model. The development model used is the ADDIE model consists of several stages: Analyze, Design, Development, Implementation, and Evaluation. Validation was done by 2 material experts, design experts and media experts. The Student Working Sheet (LKS) developed was tested in 3 stages, one to one learner with 3 subjects, small group trial try-out) with the subject of 6 students, field trial (field try-out) with the subject of 36 students. The results showed that the Student Worksheet (LKS) problem based on problem based learning based on the assessment: 1) the material experts obtained the average total of 3.98 included in the category of "Good" and if the percentage get 80% value so that included in the category " Valid ". 2) design experts obtained an average total of 4.00 which is included in the category of "Good" and in percent get the value of 80% so that included in the category "Valid". 3) media experts obtained an average total of 4.83 which is included in the category of "Very Good" and in percent score 97% so that included in the category of "Very Valid". Student assessments were conducted in 3 stages: 1) individual trials obtained an average total of 4.55 that belonged to the category of "Very Good" and in percent score of 91% so that included "Very Valid" category, 2) small group trial obtained total average of 4.65 which belongs to the category of "Very Good" and in percent get 93% value so that the category "Very Valid", 3) field trial obtained the average total 4.64 which belongs to the category "Very Good" and in percent score of 92% so it belongs to the category of "Very Valid". Thus, Student Worksheet (LKS) based on problem based learning on the number material in class VII is declared valid and practical so feasible to be used in the learning process by teachers and junior high school students especially material number.Keywords: Development, Student Worksheet (LKS), Problem Based Learning, ADDIE.